Convergent evolution of reduced eggshell conductance in avian brood parasites. (1st April 2019) - McClelland, Stephanie C.; Jamie, Gabriel A.; Waters, Katy; Caldas, Lara; Spottiswoode, Claire N.; Portugal, Steven J.
Abstract : Brood parasitism has evolved independently in several bird lineages, giving rise to strikingly similar behavioural adaptations that suggest convergent evolution. By comparison, convergence of physiological traits that optimize this breeding strategy has received much less attention, yet these species share many similar physiological traits that optimize this breeding strategy. Eggshell structure is important for embryonic development as it controls the flux of metabolic gases, such as O2, CO2 and H2 O, into and out of the egg; in particular, water vapour conductance ( G H2 O ) is an essential process for optimal development of the embryo. Previous work has shown that common cuckoos ( Cuculus canorus ) have a lower than expected eggshell G H2 O compared with their hosts. Here, we sought to test whether this is a trait found in other independently evolved avian brood parasites, and therefore reflects a general adaptation to a parasitic lifestyle. We analysed G H2 O for seven species of brood parasites from four unique lineages as well as for their hosts, and combined this with species from the literature. We found lower than expected G H2 O among all our observed brood parasites both compared with hosts (except for brown-headed cowbirds ( Molothrus ater )) and compared with the expected rates given their phylogenetic positions. These findings suggest that a lowered G H2 O may be a general adaptation for brood parasitism, perhaps helping the parasite nestling to develop greater aerobic fitness. This article is part of the theme issue 'The coevolutionary biology of brood parasitism: from mechanism to pattern'.